Incentives for improving human resource outcomes in health care: overview of reviews. (January 2014) - Misfeldt, Renee; Linder, Jordana; Lait, Jana; Hepp, Shelanne; Armitage, Gail; Jackson, Karen; Suter, Esther
Objectives: To review the effectiveness of financial and nonfinancial incentives for improving the benefits (recruitment, retention, job satisfaction, absenteeism, turnover, intent to leave) of human resource strategies in health care. Methods: Overview of 33 reviews published from 2000 to 2012 summarized the effectiveness of incentives for improving human resource outcomes in health care (such as job satisfaction, turnover rates, recruitment, and retention) that met the inclusion criteria and were assessed by at least two research members using the Assessment of Multiple Systematic Reviews quality assessment tool. Of those, 13 reviews met the quality criteria and were included in the overview. Information was extracted on a description of the review, the incentives considered, and their impact on human resource outcomes. The information on the relationship between incentives and outcomes was assessed and synthesized. Results: While financial compensation is the best-recognized approach within an incentives package, there is evidence that health care practitioners respond positively to incentives linked to the quality of the working environments including opportunities for professional development, improved work life balance, interprofessional collaboration, and professional autonomy. There is less evidence that workload factors such as job demand, restructured staffing models, re-engineered work designs, ward practices, employment status, or staff skill mix have an impact on human resource outcomes. Conclusions: Overall, evidence of effective strategies for improving outcomes is mixed. While financial incentives play a key role in enhancing outcomes, they need to be considered as only one strategy within an incentives package. There is stronger evidence that improving the work place environment and instituting mechanisms for work-life balance need to be part of an overall strategy to improve outcomes for health care practitioners.